Safety of Acupuncture in Patients Taking Newer Oral Anticoagulants: A Retrospective Chart Review Study - Kwon, Seungwon (Evid Based Complement Alternat Med, 2018)
Anticoagulant therapy is used to reduce the risk of thromboembolic events in patients with atrial fibrillation. Warfarin has been the traditional anticoagulant but is difficult to use because of its narrow therapeutic window. Recently, newer oral anticoagulants (NOACs) have been developed. However, bleeding continues to be a significant complication. The objective of this study was to assess the safety of acupuncture in patients taking NOACs. The medical records in the Stroke Center at Kyung Hee University Korean Medicine Hospital were retrospectively reviewed to identify patients who had received acupuncture between January 2017 and September 2017. The patients were divided into groups according to whether they were taking an NOAC, an antiplatelet agent, or no anticoagulant therapy. Bleeding-related side effects that occurred immediately after removal of acupuncture needles were recorded. Three hundred and sixteen patients underwent 10,177 acupuncture sessions during the study period. Microbleeding (bleeding that ceased within 30 s) occurred at a rate of 3.9% in the NOAC group, 5.6% in the antiplatelet group, and 5.1% in the control group. There were no between-group differences in the microbleeding rate. No serious adverse events, including major bleeding, were detected. These findings indicate that acupuncture is safe in patients taking NOACs.